2007
DOI: 10.1111/j.1478-3231.2007.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the pathogenesis of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an increasingly recognized cause of chronic liver disease, representing the leading cause of hepatology referral in some centres. However, its pathophysiology is not completely understood. Insulin resistance is one of the major mechanisms involved in disease prevalence and progression. Owing to the lack of an effective pharmacological therapy, recommendations on treatment are scarce and are based mainly on lifestyle changes, including diet and exercise. A review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 111 publications
2
101
0
7
Order By: Relevance
“…41,42 Consequently, lean subjects have high levels, whereas obese subjects have low plasma levels. Decreased expression of adiponectin is observed in a number of obesity-related co-morbidities such as type 2 diabetes, 43,44 the metabolic syndrome, 45,46 non-alcoholic steatohepatitis 16 and CAD. 47,48 It has also been found that the protein is anti-diabetic, increasing insulin sensitivity, glucose uptake and fat oxidation, as well as suppressing hepatic glucose output.…”
Section: Adipose Tissue a Paracrine And Endocrine Organmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Consequently, lean subjects have high levels, whereas obese subjects have low plasma levels. Decreased expression of adiponectin is observed in a number of obesity-related co-morbidities such as type 2 diabetes, 43,44 the metabolic syndrome, 45,46 non-alcoholic steatohepatitis 16 and CAD. 47,48 It has also been found that the protein is anti-diabetic, increasing insulin sensitivity, glucose uptake and fat oxidation, as well as suppressing hepatic glucose output.…”
Section: Adipose Tissue a Paracrine And Endocrine Organmentioning
confidence: 99%
“…Excessive fat accumulation in the visceral stores leads to the secretion of free fatty acids into the portal vein, which, with the secretion of pro-inflammatory adipokines, leads to hepatic insulin resistance and aberrant accumulation of lipids in hepatocytes and the resultant hepatic steatosis. 16 In obese individuals, the inadequate lipid storage capacity of the body's adipose tissue depots leads to ectopic fat deposition not only in the liver but in other organs such as skeletal muscle and the insulin secreting b-cells of the pancreas. It has been suggested that this ectopic fat deposition may play an important role in the aetiology of both insulin resistance and b-cell failure.…”
Section: A Changing View Of Adiposity Through the Agesmentioning
confidence: 99%
“…2 The predominant view of the disease pathophysiology points to the occurrence of a sequential evolution from bland steatosis to NASH due to either a second hit or to worsening of insulin resistance. 24,25 This view might be wrong and the possibility exists that patients with bland steatosis belong to a completely different population than those with NASH from the very beginning of the disease. Recent data suggesting that hepatic steatosis may indeed protect against the development of advanced disease is in line with this view.…”
mentioning
confidence: 99%
“…is present according to the "second hit" theory. 25 These data also help to explain why steatosis often decreases or disappears in the advanced stages of the disease ("burned NASH"). 1 The recent finding by Romeo et al 27 that variations of the PNPLA3 (Patatin-like phospholipase domain containing 3) gene, which encodes a triacylglycerol lipase that mediates triac-ylglycerol hydrolysis in both adipose tissue and the liver, contribute to the observed interindividual differences in hepatic fat content is in line with the concept of good and bad hepatic fat storers.…”
mentioning
confidence: 99%
“…< adaptative qui fragilise les cellules, les rendant ainsi plus sensibles aux agressions telles que le stress oxydatif, la peroxydation lipidique et certaines cytokines conduisant à l'inflammation et à la fibrose. Ainsi, bien que chez certains individus, la stéatose demeure béni-gne, elle évolue en stéato-hépatite chez 10 à 20 % des patients obèses et résistants à l'insuline [3]. Lors du développement de la stéatose hépatique, les lipides qui s'accumulent dans le foie sont majoritairement des triglycérides, issus de l'estérification de trois acides gras avec un glycérol-3-phosphate.…”
Section: Implication Du Facteur De Transcription Chrebpunclassified